2020
DOI: 10.1177/1744806920918057
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of neuroglial interactions using differential target multiplexed spinal cord stimulation in an animal model of neuropathic pain

Abstract: The development and maintenance of chronic neuropathic pain involves distorted neuroglial interactions, which result in prolonged perturbations of immune and inflammatory response, as well as disrupted synapses and cellular interactions. Spinal cord stimulation (SCS) has proven effective and safe for more than 40 years, but comprehensive understanding of its mode of action remains elusive. Previous work in our laboratory provided evidence that conventional SCS parameters modulate biological processes associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(120 citation statements)
references
References 57 publications
2
117
0
1
Order By: Relevance
“…As previously reported, the pain model sets an immune and inflammatory response that involves glial cells. 3,13 The larger effect on microglia reflects the early stage of the development of chronic pain in our model. By the time tissues are dissected, animals in the FDR: false discovery rate.…”
Section: Effect Of the Pain Model In The Cell-specific Transcriptomesmentioning
confidence: 96%
“…As previously reported, the pain model sets an immune and inflammatory response that involves glial cells. 3,13 The larger effect on microglia reflects the early stage of the development of chronic pain in our model. By the time tissues are dissected, animals in the FDR: false discovery rate.…”
Section: Effect Of the Pain Model In The Cell-specific Transcriptomesmentioning
confidence: 96%
“…Balanced, biphasic stimulation with a phase pulse width of under 200 µs on 1×8 percutaneous SCS leads provides a reasonable range of pulse width choices for the newest stimulation paradigms, such as those applied in recent bioinformatics work in SCS in preclinical models, while simultaneously providing for high-fidelity resolution of the N1/P2 features of the ECAP. 25 Where longer pulse widths are desired to optimize coverage for paresthesiabased SCS therapies, for instance, caution is warranted to ensure the reported ECAP truly represents neural activation versus merely misclassification of stimulation artifact or other non-physiologic noise. 26…”
mentioning
confidence: 99%
“…Behavioral and molecular biology-based results from these studies have shown that the multiplexed programming approach may be more effective than standard and high-frequency (1,200-Hz) SCS programming. 7 Certain aspects of the feasibility study design deserve further discussion. Programming of standard SCS was assisted by a representative from the manufacturer of the commercially available SCS system, while a representative from the sponsor of the study assisted with the multiplexed programming.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] A new programming approach that has shown significant promise in preclinical studies is based on a Differential Target Multiplexed approach that uses multiple electrical signals that can be different from one another in aspects such as frequencies, pulse rates, and amplitudes. 7 It is the first programming approach that has been shown to be significantly better than lowrate (50-Hz) programming and high-rate (1, programming in all 3 pain-like behavior experiments (mechanical, cold, and heat hypersensitivity) using the spared nerve injury model of neuropathic pain in rats. In this model, the Differential Target Multiplexed programming approach modulated more chronic pain related biological processes back toward their state in uninjured, non-implanted (na€ ıve) animals than low-rate programming and high-rate programming.…”
Section: Introductionmentioning
confidence: 99%